Cultural heritage in the educational practice of the school museum (on the example of the museum of the history of the village of Pogorilivka in Ukraine) - Lyudmila GERUS (Dialogica: Revistă de Studii Culturale și Literatură, 2022)
In the article was revealed the problem of preserving cultural heritage with the help of school museum. The prerequisites for the creation of the school Museum of the History of the village of Pogorilivka (Ukraine), its museum space and expositions (“History of the village, rural house, everyday life and weaving”, “Room of ethnography”, “Svetlitsa (front room) of bread”) were considered. The village of Pogorilivka in Bukovina is one of the Ukrainian villages that have not lost their self-sufficiency and identity. The locality represents an ethnographic and folkloric valuable area, which led to the establishment of the School Museum of Village History. The main directions of the Museum’s activity were analyzed as an element of the social structure that allows to learn, teach, educate, affirming ethnic identity. Conclusions were drawn about the fundamental practices of museum pedagogy. The importance of representative ethnic cultural symbols was determined; the need for their search was emphasized, possible ways of their active implementation in educational programs and in the modern socio-cultural environment was indicated. One of the central representative ethnic symbols of Ukrainians was identified ritual bread, widely represented in the “Svetlitsa (front room) of bread” of the Museum of the History of the village of Pogorilivka.